Advertising, promotion, and other aspects of integrated marketing communications - Andrews, J. Craig; Shimp, Terence A. (Australia United States Cengage, 2025)
"Advertising, Promotion, and other aspects of Integrated Marketing Communications is intended for use in undergraduate or graduate courses in marketing communications, advertising, promotion strategy, promotion management, or other courses with similar concentrations. Professors and students alike should find this book substantive, but highly readable, eminently current but also appreciative of the evolution of the field"-- Provided by publisher.
Previous editions: 2018, 2013.
Includes bibliographical references (pages 608-671) and indexes.
Keywords: Communication in marketing -- Textbooks; Direct marketing; Sales promotion; Advertising